Taxation and technology transfer : key issues (UN New YorkUS, 2005)
Provides an overview of the impact of taxation in developed and developing countries on the transfer of technology. Seeks to shed light on the formulation of tax policies that could facilitate technology transfer. Presents extensive national tax policy options designed to facilitate technology transfer, along with several government initiatives, measures and institutions, as well as incentives provided to industry aimed at facilitating the transfer of technology.
Keywords: TAXATION